GAMBARAN PERILAKU KONSUMTIF TERHADAP SEPATU PADA PEREMPUAN DEWASA AWAL - Riyan Adiputra; Clara Moningka (Psibernetika, 2012)
In this research, researcher want to find out description consumptive behavior about footwear to female early adulthood. This research into descriptive quantitative which the aim is find out decription consumptive behavior about footwear to female early adulthood. The sample is female early adulthood (20 – 40 years old) who shopping in shopping centre which in Jakarta city. Sampling technique using non-probability sampling by sampling convenient and total samples are 100 female early adulthood. This research using consumptive behavior scale reviewed from Sumartono’s indicator (2002). Reliability values are .849. Analyzed by statistic descriptive. The cloncusion is that consumptive behavior about footwear to female early adulthood disposed low. Keywords: Consumptive behavior, Footwear, Female early adulthood.